PIAGAM MADINAH SEBAGAI PILAR DASAR KERUKUNAN MASYARAKAT MADINAH - Muhammad Fakhri (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
Medina Charter have to accommodate the interests of Jews, Christians and the tribes in Medina. Thus, through the Charter of Medina creates unity and brotherhood between the immigrants and the Ansar, as well between tribes and religions that flourished in Medina. Thus, the harmony which successfully realized by the Prophet Muhammad, through the Charter of Medina, is the harmony between religions, religious internal harmony , harmony between religious communities by the State